2023
DOI: 10.1007/s10461-023-03982-9
|View full text |Cite
|
Sign up to set email alerts
|

Individual-, Interpersonal- and Institutional-Level Factors Associated with HIV Stigma Among Youth in Kenya

Abstract: HIV stigma remains a barrier in achieving optimal HIV treatment. We studied the prevalence and predictors of HIV stigma among adolescents and youth with HIV (AYWHIV) ages 15–24 years in Western Kenya. Of 1011 AYWHIV, 69% were female with a median age of 18 years. Most (59%) attended adolescent clinic days, and 40% attended support groups. One-quarter (27%) had experienced physical, 18% emotional, and 7% sexual violence. The majority of AYWHIV (88%) reported disclosure concerns, 48% reported perceived community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…A few studies have investigated the reverse relationship, for example demonstrating that poor mental health was associated with higher HIV stigma [25,26]. In this study, we investigated this 'reverse' relationship using baseline data and showed that YWH with depressive symptoms had higher overall stigma scores than those without depressive symptoms [51]. In a longitudinal study from a cohort of adults from multiple SSA countries, good treatment adherence was associated with a steeper decline in mean HIV stigma over time [41].…”
Section: Discussionmentioning
confidence: 92%
“…A few studies have investigated the reverse relationship, for example demonstrating that poor mental health was associated with higher HIV stigma [25,26]. In this study, we investigated this 'reverse' relationship using baseline data and showed that YWH with depressive symptoms had higher overall stigma scores than those without depressive symptoms [51]. In a longitudinal study from a cohort of adults from multiple SSA countries, good treatment adherence was associated with a steeper decline in mean HIV stigma over time [41].…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, the study findings showed that participants of secondary educational level and aged 10–19 years had a high proportion of internalized stigma (40/58) and (36/58) respectively. On the contrary, findings from available studies showed dropping out of school increases internal stigma among the AYLHIV [ 22 ]. The study finding could be attributed to the levels of social support from the participants’ schoolmates, teachers, and friends.…”
Section: Discussionmentioning
confidence: 99%
“…Stigma exists in Indonesia, particularly for women living with HIV, and it is the primary cause of non-adherence to ART (Ismail et al, 2022 ; Nurfalah et al, 2019 ; Yona et al, 2021 ). Internal factors, such as lack of motivation and forgetfulness, were also mentioned as barriers to ART adherence (Mugo et al, 2023 ; Sefah et al, 2022 ; Shrestha et al, 2019 ). A mixed-method study by Sefah et al ( 2022 ) found that lower adherence to ART was associated with patients’ belief in herbal medicine and, from qualitative analysis, low motivation arising from pill fatigue, forgetfulness, frequent stock out of drugs, long waiting times, and worrying side-effects became barriers to ART adherence.…”
Section: Discussionmentioning
confidence: 99%